A new modulation strategy for a buck-boost input AC - Morrison, R.
This paper presents a novel modulation strategy for a power factor corrected (PFC), isolated AC/DC converter derived from the integration of a nonisolated, two switch buck-boost AC/DC converter with an isolated dual active bridge DC/DC converter (2SBBDAB). This strategy, termed discontinuous leading/trailing edge (DLTE) modulation, serves to maximize the duty cycle of the input switch while keeping the current in the buck-boost inductor discontinuous. Hence, the crest factors of the currents in the switching devices are minimized, the input switch is turned on at zero current and the zero-voltage switching ranges of the bridge switches are unaffected by the integration. A conventional isolated, PFC AC/DC converter typically consists of a boost converter cascaded with a forward converter. The ratings required of the power switching devices of the 2SBBDAB employing the DLTE modulation strategy are similar to those required of the conventional design for wide line voltage operation. However, the 2SBBDAB converter has higher line voltage surge immunity than that of the conventional design and, unlike the conventional design, it has inherent inrush current limiting. The DLTE modulation strategy may be applied to the family of converters composed of the two switch buck-boost integrated with half and full-bridge forward converters
Keywords: Boost converter; Bridge switches; Buck-boost inductor; Buck-boost input AC/DC converter; Current crest factors; Discontinuous leading/trailing edge modulation; Forward converter; Full-bridge forward converters; Half-bridge forward converters; Input switch duty cycle maximisation; Inrush current limiting; Isolated AC/DC converter; Isolated dual active bridge DC/DC converter; Modulation strategy; Nonisolated two switch buck-boost AC/DC converter; Power factor correction; Switching devices; Voltage surge immunity; Wide line voltage operation; Zero-voltage switching